Gender perceptions of benefits and challenges of online learning in Malaysian ESL classroom during COVID-19 - Khalilah Ramli; Aladdin Assaiqeli; Nor Azmi Mostafa; Charanjit Kaur Swaran Singh (Studies in English Language and Education, 2022)
The current study aims to investigate students’ perceptions of the benefits and challenges of online learning implementation in ESL classrooms and how gender differences influence their perceptions. Participants were 60 undergraduate students from a private university in Perak, Malaysia, who enrolled in English language courses taken during the shift to online learning at the institution. The study utilizes a quantitative approach where data were collected using an adapted questionnaire in the form of Google Form. Data collected were analysed with independent samples t-test using the SPSS software. Overall, the majority of the students agreed that the implementation of online learning posed challenges for them. The students, however, showed unbiased opinions towards the benefits of the online learning implementation in the ESL classrooms. Based on the analysis, the study found that gender differences do not influence the students’ perceptions of the benefits and challenges of online learning. The findings indicated that students do face difficulties in learning online and that there is a need for the lecturers to improve the teaching practices and strategies for online learning. The institution management is also recommended to provide better resources and technical support for effective online learning.